Effect of Weave Pattern on Experimental and Simulated Ballistic Behavior of Carbon Fiber Reinforced Polybenzoxazine Composites - Inthakun, Kangsadan (Naresuan University Engineering Journal, 2024)
This research investigates the effect of weave patterns on the experimental and simulated ballistic performance of carbon fabric reinforced polybenzoxazine (CFR-poly(BA-a)) composites. The present study focuses on developing the materials using a strike panel impacted by a rigid 7.62×51 mm projectile at an impact velocity of 847±9.1. This study compares the ballistic performance of three different weave patterns of CFR-poly(BA-a) composite against the penetration of a 7.62×51 mm projectile by using an energy absorption equation that includes fiber/matrix cohesive failures to predict the appropriate thickness of the composite to protect against penetration. The damage area of the specimen composites is also studied using numerical simulation by using parameters of material properties composite under impact event using 7.62×51 mm projectiles and was performed on 4, 8, and 12 plies of CFR-poly(BA-a) composite. Laminates of three different carbon fabric weave patterns were fabricated using plain, 2x2 twill and unidirectional weaves. The ballistic performance of the composites was investigated by using CFR-poly(BA-a) composite as a strike panel dimensions 150 x 150 mm. The damage area of the specimen composites observed from the experiment results are in good agreement with the numerical simulation model, the error in the prediction of the damage pattern of the specimen composite was less than 3%. The numerical simulation model effectively anticipates the qualitative extent of damage for the composite specimen. The ballistic performance of the composite panel reinforced with a twill weave pattern of carbon fiber observed from the experiment result was superior to that of other weave patterns of carbon fiber due to the 2D woven structure being able to transmit load simultaneously in longitudinal and transverse weave directions. Therefore, it resisted stiffness, stress, and stress distribution. In addition, the twill weave pattern had low contact friction, crimp, and binding effect because of its minimum intersection point compared with plain weave and unidirectional fabrics, therefore relatively high mechanical properties, high energy absorption, and better protection against penetration of the impact velocity of the projectile on the ballistic performance, while also being thinner and lighter when compared with other weaves. These properties make it a more effective material for use in ballistic applications. The numerical simulation and experimental results of the ballistic performance reveal that the hardness of the three weave patterns of CFR-poly(BA-a) composites were able to effectively protect against a single projectile shot without penetration on the rear side of the strike panel, the penetration depth, and damage extent of the perforation were in good agreement with the numerical simulation model. These results suggest the composite could be developed and applied as a strike panel in hard ballistic armor. The findings demonstrate a correlation between numerical simulation outcomes from ballistic impact tests and experimental results, effectively predicting the behavior of CFR-poly(BA-a) composites with relatively low error and good correlation with the experimental data. This predictive capability allows for safe, rapid, and cost-effective design validation and testing by leveraging virtual ballistic impact test models of real-world assets for a person interested in studying them in the future.